Preventing Ventilator-Associated Pneumonia in a Pediatric Intensive Care Unit using a Modified Ventilator-Associated Pneumonia Bundle: Pre-interventional and Post-interventional Trial - Alaa Obeid; Raymond Kamel; Amal Naous; Bassem Abou Merhi; Mariam Rajab (International Journal of Medical Research, 2014)
Background: Ventilator-associated pneumonia increases in-hospital stay, morbidity and mortality of ventilated pediatric patients. It prolongs time spent on the ventilator and length of Pediatric Intensive Care Unit stay. Methods: This is a pre-interventional and post-interventional trial of 57 and 50 pediatric patients, respectively, which started in March 2011 to decrease the rate of ventilator-associated pneumonia in Pediatric Intensive Care Unit after initiation of a modified pediatric VAP bundle compared with the ventilator-associated pneumonia rate for the preceding 12 months. The study was conducted at Makassed General Hospital in Beirut, Lebanon. It included pediatric patients that were on mechanical ventilation from March 2010 to March 2012. An interdisciplinary performance improvement team was formed, who implemented a modified pediatric VAP bundle. Results: The implementation of the pediatric VAP bundle resulted in the reduction of ventilator-associated pneumonia rates from 52% (March 2010-2011) to 6% (March 2011-2012) (P<0.001).Patients who had VAP had longer stay on mechanical ventilation with a mean of 11.42 ventilator-days than those who didn’t develop ventilator-associated pneumonia with a mean of 5.18 ventilator-days (P<0.0001). Conclusion: Implementing the modified pediatric VAP bundle significantly reduced the ventilator-associated pneumonia rate, time on mechanical ventilation and hospital length stay with potential decrease in cost.